2017
DOI: 10.1186/s12906-017-1704-5
|View full text |Cite
|
Sign up to set email alerts
|

Tonggyu-tang, a traditional Korean medicine, suppresses pro-inflammatory cytokine production through inhibition of MAPK and NF-κB activation in human mast cells and keratinocytes

Abstract: BackgroundAllergic diseases including allergic rhinitis, asthma, and atopic dermatitis are increasing worldwide. Common medications used to treat these inflammatory disorders are anti-histamines and corticosteroids, but they have their own limitations such as short duration and severe side effects. Thus, interest in complementary and alternative medicine is continually growing. Here, we investigate the anti-inflammatory mechanisms of Tonggyu-tang (TGT), a traditional Korean medicine that has been used to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Some studies also showed that herbal decoctions could reduce the release of inflammatory factors in allergic diseases and keratinocytes by inhibiting mitogen-activated protein kinase and NF-jB pathways. 32,33 In addition, the decoction composed of AM and angelica sinensis could inhibit the NF-kB pathway and reduce allergic inflammation of the skin. 34 In our study, OVA significantly increased the mRNA expression of p65, while AM significantly decreased this trend.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also showed that herbal decoctions could reduce the release of inflammatory factors in allergic diseases and keratinocytes by inhibiting mitogen-activated protein kinase and NF-jB pathways. 32,33 In addition, the decoction composed of AM and angelica sinensis could inhibit the NF-kB pathway and reduce allergic inflammation of the skin. 34 In our study, OVA significantly increased the mRNA expression of p65, while AM significantly decreased this trend.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK can transmit signals from receptors on the cell surface to DNA in the nucleus and participate in biological processes, such as cell growth, death, and cell cycle, and also in the regulation of pathological processes, such as inflammation and stress response. As a member of the MAPK family, MAPK3 plays an important role in the process of proliferation, differentiation, and formation of inflammatory cells [ 33 , 34 ]. PTGS2 is an inducible immediate response gene that is not expressed in most cells under normal physiological conditions, but during pathological reactions such as inflammation or tumors, the expression of PTGS2 is rapidly upregulated, producing a large amount of prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are closely associated with the expression of inflammatory cytokines and chemokines upon pathogen challenge. The phosphorylation of ERK, JNK and p38 MAPKs can also activate NF-Κb ( 26 ). Previous studies have suggested that Evo inhibits the migration and invasiveness of NPC cells accounting for the inactivation of NF-κB and MAPKs ( 27 ).…”
Section: Discussionmentioning
confidence: 99%